2008
DOI: 10.1007/s10530-008-9372-5
|View full text |Cite
|
Sign up to set email alerts
|

The diversity of juvenile salmonids does not affect their competitive impact on a native galaxiid

Abstract: We used an invaded stream fish community in southern Chile to experimentally test whether the diversity of exotic species affects their competitive impact on a native species. In artificial enclosures an established invasive, rainbow trout, Oncorhynchus mykiss, and a potential invader, Atlantic salmon, Salmo salar, reduced the growth rate of native peladilla, Aplochiton zebra, by the same amount. In enclosures with both exotic salmonids, the growth rates of all three species were the same as in single exotic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…In our surveys of island streams, we have encountered five native species: four galaxiids -Galaxias maculatus (ubiquitous and abundant in intertidal zones), Brachygalaxias bullocki (rare and scarce), Aplochiton zebra (variable), Aplochiton taeniatus (rare and scarce), and a native lamprey -Geotria australis (rare with juveniles locally common). Our study compares the impacts of rainbow and brown trout on Aplochiton spp., two diadromous drift feeders whose life histories, ecologies and conservation status remain poorly understood (McDowall & Nakaya, 1988;Dyer, 2000;Cussac et al, 2004;McDowall, 2006;Lattuca et al 2008;Young et al 2009). …”
Section: Study Areamentioning
confidence: 99%
“…In our surveys of island streams, we have encountered five native species: four galaxiids -Galaxias maculatus (ubiquitous and abundant in intertidal zones), Brachygalaxias bullocki (rare and scarce), Aplochiton zebra (variable), Aplochiton taeniatus (rare and scarce), and a native lamprey -Geotria australis (rare with juveniles locally common). Our study compares the impacts of rainbow and brown trout on Aplochiton spp., two diadromous drift feeders whose life histories, ecologies and conservation status remain poorly understood (McDowall & Nakaya, 1988;Dyer, 2000;Cussac et al, 2004;McDowall, 2006;Lattuca et al 2008;Young et al 2009). …”
Section: Study Areamentioning
confidence: 99%
“…Also, McDowall et al [44], [45] described the diet and morphological adaptations of putative AZ living in an endorheic, turbid lake on Falkland Islands, yet it turned out that when Vanhaecke et al [7] barcoded individuals from that same site (Red Pond), they only found AT. This is an example of likely misidentification, and, it is possible that other studies addressing the biogeography, ecology and biology of putative AZ might have inadvertently examined AT [4], [5], [43], [46][48]. Future work should critically reframe relevant background knowledge whenever Aplochiton species identity matters.…”
Section: Resultsmentioning
confidence: 99%
“…Galaxiids are confined to the Southern Hemisphere and are evolutionarily naive with respect to the salmonid predators that have been deliberately introduced from the Northern Hemisphere (Cox & Lima, 2006;Mcdowall, 2006). Although direct predation is probably the leading cause of these negative effects, some indirect effects have also been documented, including habitat shifts (Mcintosh, Townsend & Crowl, 1992;Edge, Townsend & Crowl, 1993;Penaluna, Arismendi & Soto, 2009) and reduced growth (Young et al, 2008). Although direct predation is probably the leading cause of these negative effects, some indirect effects have also been documented, including habitat shifts (Mcintosh, Townsend & Crowl, 1992;Edge, Townsend & Crowl, 1993;Penaluna, Arismendi & Soto, 2009) and reduced growth (Young et al, 2008).…”
Section: Introductionmentioning
confidence: 99%